FRAMING ANALYSIS OF CAPRES 1 DEBATE IN COMPASS AND MEDIA DAILY INDONESIA - Heri Hendriana; Deden Ahmad Hidayat; Rochmat Tri Sudrajat (IKIP Siliwangi, 2020)
Analysis of news text discourse that emphasizes the constellation of forces that occur in the production and reproduction of news media. The research approach used is the Framing analysis approach. Data Analysis of this critical discourse is a news fragment in the form of paragraphs in the news, Media Indonesia and Kompas are more directed to existing powers, Media Indonesia and Kompas have special considerations in the selection of issues presented to readers every day. Critical discourse analysis places media as a source of information that creates and reality with the grammar used and choices of diction so as to give birth to a diverse representation of information for the audience.